Abnormal tibial position is correlated to early degenerative changes one year following ACL reconstruction. Issue 7 (21st May 2015) - Zaid, Musa; Lansdown, Drew; Su, Favian; Pedoia, Valentina; Tufts, Lauren; Rizzo, Sarah; Souza, Richard B.; Li, Xiaojuan; Ma, C. Benjamin
ABSTRACT Altered knee kinematics following ACL reconstruction may predispose patients to the development of early onset post‐traumatic osteoarthritis. The goal of our study was to examine the longitudinal interrelationship between altered tibial position relative to the femur and cartilage health measured by quantitative T1ρ MRI. Twenty‐five patients with isolated unilateral ACL injury underwent kinematic and cartilage T1ρ MRI at baseline prior to ACL reconstruction and then at 1‐year post‐reconstruction. Tibial position relative to the femur in the anterior–posterior plane was calculated as well as cartilage T1ρ relaxation values in the injured and uninjured knee. At baseline prior to ACL reconstruction, the tibia was in a significantly more anterior position relative to the femur in the ACL deficient knee compared to the healthy contralateral knee. This difference was no longer present at 1‐year follow‐up. Additionally, the side–side difference in tibial position correlated to increased cartilage T1ρ relaxation values in the medial compartment of the knee 1‐year post‐reconstruction. Altered tibial position following ACL reconstruction is correlated with detectable cartilage degeneration as soon as 1 year following ACL reconstruction. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1079–1086, 2015.